Occurrence of Hyperkalemia in Patients with Chronic Kidney and Liver Diseases: Hyperkalemia in Chronic Kidney and Liver Diseases - Sheikh, Farzana Adnan; Razzak, Asma; Qamar, Mehwish; Qureshi, Maria (Pakistan Journal of Health Sciences, 2024)
Hyperkalemia is a common and potentially life-threatening electrolyte imbalance in patients with Chronic Kidney Disease (CKD) and Chronic Liver Disease (CLD), often exacerbated by comorbid conditions such as hypertension and diabetes. Objective: To assess the frequency and risk factors associated with hyperkalemia in patients with Chronic Kidney Disease (CKD) and Chronic Liver Disease (CLD) at a tertiary care hospital in Karachi, Pakistan. Methods: This cross-sectional study was carried out from March 2024 to May 2024, including 120 adult patients diagnosed with CKD (stage 3 or above) or CLD. Data on demographics, disease duration, comorbidities, previous hyperkalemia episodes, and medication compliance were collected. Serum potassium levels were measured, with hyperkalemia severity classified as mild (K+ 5.0–5.5 mEq/L), moderate (K+ 5.5–6.0 mEq/L), or severe (K+ >6.0 mEq/L). Statistical analysis was performed using SPSS version 24.0, with Spearman correlation and Chi-square tests applied. Results: The average age of the patients was 53.33 years, with 55% being male. The mean serum potassium level was 5.42±0.92 mEq/L. Medication compliance was high in 74.2% of patients. Hyperkalemia was present in 70.8% of patients, with 22.5% exhibiting severe hyperkalemia. Significant association was found between severity of hyperkalemia and age (p<0.01). Hypertension (p=0.001) and diabetes mellitus (p=0.001) were significantly associated with severity of potassium levels. Conclusion: The study highlighted a high prevalence of hyperkalemia in CKD and CLD patients, significantly associated with age, hypertension, and diabetes mellitus.